Help-seeking behaviour and adolescent self-harm: A systematic review. (December 2014) - Rowe, Sarah L; French, Rebecca S; Henderson, Claire; Ougrin, Dennis; Slade, Mike; Moran, Paul
Objective: Self-harm is common in adolescence, but most young people who self-harm do not seek professional help. The aim of this literature review was to determine (a) the sources of support adolescents who self-harm access if they seek help, and (b) the barriers and facilitators to help-seeking for adolescents who self-harm. Method: Using a pre-defined search strategy we searched databases for terms related to self-harm, adolescents and help-seeking. Studies were included in the review if participants were aged 11–19 years. Results: Twenty articles met criteria for inclusion. Between a third and one half of adolescents who self-harm do not seek help for this behaviour. Of those who seek help, results showed adolescents primarily turned to friends and family for support. The Internet may be more commonly used as a tool for self-disclosure rather than asking for help. Barriers to help-seeking included fear of negative reactions from others including stigmatisation, fear of confidentiality being breached and fear of being seen as 'attention-seeking'. Few facilitators of help-seeking were identified. Conclusions: Of the small proportion of adolescents who seek help for their self-harm, informal sources are the most likely support systems accessed. Interpersonal barriers and a lack of knowledge about where to go for help may impede help-seeking. Future research should address the lack of knowledge regarding the facilitators of help-seeking behaviour in order to improve the ability of services to engage with this vulnerable group of young people.